Long‐Term Randomized Trial of Intensive Versus Symptomatic Management in Paget's Disease of Bone: The PRISM‐EZ Study. (8th February 2017) - Tan, Adrian; Goodman, Kirsteen; Walker, Allan; Hudson, Jemma; MacLennan, Graeme S; Selby, Peter L; Fraser, William D; Ralston, Stuart H; ,
ABSTRACT: It has been suggested that normalization of bone turnover may improve clinical outcome in Paget's disease of bone (PDB) by preventing complications such as fractures and the development of osteoarthritis. Here we investigated the long‐term effects of a treatment strategy that aimed to normalize bone turnover in PDB with that of symptomatic treatment. The study group comprised 502 subjects who were enrolled into a 3‐year extension of the Paget's Disease: Randomized Trial of Intensive versus Symptomatic Management (PRISM) study. Intensive bisphosphonate therapy was continued in 270 of these subjects with the aim of normalizing bone turnover using zoledronic acid as the treatment of first choice. Symptomatic treatment continued in 232 subjects in whom bisphosphonates were only given for the treatment of bone pain. The primary outcome was fracture and secondary outcomes were orthopedic procedures, quality of life, and bone pain, adjusted for baseline characteristics. Serum total alkaline phosphatase (ALP) concentrations were significantly lower in the intensive group on entry to the study and the differences between groups increased as the study progressed. There were no clinically important differences in quality of life measures or bone pain between the treatment groups. Intensive treatment was associated with a nonsignificant increase in fracture risk (hazard ratio = 1.90; 95% CI, 0.91 to 3.98; p = 0.087), orthopedic procedures (1.81; 95% CI, 0.71 to 4.61; p = 0.214), and serious adverse events (relative risk 1.28; 95% CI, 0.96 to 1.42). We conclude that long‐term intensive bisphosphonate therapy confers no clinical benefit over symptomatic therapy and is associated with a nonsignificant increase in the risk of fractures, orthopedic events, and serious adverse events. The results of this study suggest that in patients with established PDB, bisphosphonate therapy should focus on control of symptoms rather than suppression of bone turnover. © 2016 American Society for Bone and Mineral Research.